The biology and the ecology of the South African mackerel, Scomber japonicus Houttuyn, and an analysis of the mackerel fishery in South Africa, 1954 - 1973 - Baird, D.(Daniel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1974.